Perplexities of Consciousness - Schwitzgebel, Eric (Book collections on Project MUSE., 2011)
In this book, the author examines various aspects of inner life (dreams, mental imagery, emotions, and other subjective phenomena) and argues that we know very little about our stream of conscious experience. In fact, he contends, we are prone to gross error about our ongoing emotional, visual, and cognitive experiences.